Developmental exposure to paraquat and maneb can impair cognition, learning and memory in Sprague-Dawley rats. Issue 10 (27th July 2016) - Li, Bai; He, Xi; Sun, Yan; Li, Baixiang
Abstract : PQ–MB may affect the behavior and cognitive function of rat offspring through the cAMP–PKA–CREB signaling pathway. Abstract : Paraquat and maneb are identified environmental pollutants. Combined exposure to paraquat and maneb is a latent risk factor for many diseases, particularly those of the central nervous system, including Parkinson's disease and Alzheimer's disease. Hippocampus is the key structure in memory formation and babies are more sensitive to environmental stimuli than adults, so we investigated the neurotoxicity of paraquat and maneb on the hippocampi of rat pups. Female and male Sprague-Dawley rats were mated (female : male = 2 : 1) every night for a week. The gravid rats were randomly divided into three groups (one control and two experimental groups). A mixed solution of paraquat–maneb was administered twice a week by lavage at a dose of 10 or 15 mg kg −1 bodyweight (containing 30 or 45 mg kg −1 bodyweight maneb, respectively) from day 6 after pregnancy till ablactation. Maternal weight gain and offspring bodyweights were not affected by the drugs. However, behavioral tests showed that reaction latency and mistake frequency increased after treatment. Intuitively, we found significant changes in the hippocampal neurons in the morphological observation. Taking into account the interaction of the related genes in the cAMP–PKA–CREB pathway, we used a variety of methods to detect the gene and protein levels. Reduced expression of cAMP and related genes and proteins in the hippocampus and serum was also observed. These results indicate that PQ–MB stimulates cAMP to reduce the production of PKA, thus reducing the phosphorylation of CREB and inhibiting the activation of other elements (BDNF, C-JUN, and C-FOS). These changes lead to hippocampal damage and impaired abilities (learning, cognition, and memory). Our results demonstrate that PQ–MB induces hippocampal toxicity in the early life of rats, and they thus provide a theoretical foundation for further investigation of the bathypelagic mechanism involved and measures that can be taken to avoid PQ–MB neurotoxicity.